Hydrography and currents on the Pernambuco Continental Shelf - Domingues,Ernesto de Carvalho (2017)
ABSTRACT The present study presents the seasonal hydrography and currents of the Brazilian Northeast Continental Shelf. The study area is located on the Brazilian tropical coast of the Atlantic Ocean between 7.5 and 9 °S. This continental shelf is narrow (~35 km wide) and shallow, with shelf break lying at a depth of 60 m. Salinity and temperature data were collected monthly by means of hydrographic surveys, conducted across the shelf in a single transect in the central part of the study area, between March 2012 and May 2013. Two further campaigns were also conducted to characterize the winter (August 2013) and the summer (January 2014), covering the whole study area (4,600 km2). Water level and currents were measured using an array of Acoustic Doppler Current Profilers (ADCP) moored at mid-shelf in the central area. Seasonal temperature ranged from 26 °C in September to 29.5 °C in April, with a 2-month lag between the minimum and maximum air temperatures. Salinity did not present a clear seasonal pattern, fluctuating between 36.5 and 37.0 psu throughout the year. The mean temperature and salinity values obtained in the winter and summer campaigns were 26.5 and 27.6 °C and 37.1 and 36.7 psu, respectively. Tropical Water (TW) was predominant, accounting for 95% to 97%, with presence of Coastal Water (CW) limited to the inner part of the shelf. The mean flow velocity values in the water column in winter and summer were 0.11 and 0.06 m/s, respectively, similarly to the seasonal wind regime. Northward currents were observed predominantly in winter, with a short period of inverted southward current. These episodes were related to periods of wind relaxation and presented periodicity of 6-13 days, observed through wavelet analysis. This periodicity may be associated with atmospheric instabilities at higher latitudes. Summer currents were sluggish, when the tides accounted for 75 and 43% of the variance in the cross- and along-shelf current components, respectively. TW is the main water mass in the Pernambuco Continental Shelf (PCS) in summer and winter. Current intensity is weak and without direction in summer and stronger towards the north in winter.